ANALISIS PERAN GURU MENUMBUHKAN SIKAP TOLERANSI DALAM PEMBELAJARAN SOSIOLOGI - Jurnawan, Hendri; Salim, Izhar; Al Hidayah, Riama (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis thesis is titled Analysis of the Role of Teachers Growing Tolerance in Learning Sociology in Class X SMA Negeri 9 Pontianak . The problem in this study is How the Role of Teachers Foster Tolerance Attitudes in Learning in Class X SMA Negeri 9 Pontianak. The method used is descriptive method. The form of research is qualitative description. Data collection techniques in this study are: direct communication with data collection tools interview guidelines, direct observation with data collection tools observation sheets, documentary studies with data collection tools school data files. The results of the study are as follows: 1) Sociology teachers provide time to chat with students related to differences and foster an attitude of tolerance. 2) The teacher's role as a mediator, the Sociology Teacher provides an example by establishing good relations and harmony to other teachers. Sociology teachers do not discredit and discredit when teaching and learning activities. 3) The Role of Teachers as Motivators, In this study conducted in Pontianak 9 High School, researchers found several roles of Sociology teachers as motivators in fostering tolerance in SMA 9 Pontianak, namely: 2 ) The teacher motivates students to invite children to make work on invitations to tolerate and students take the initiative to make large banners posted on the walls of the classroom in the hope that students are motivated. 2) The teacher invites all students to work together.Keyword : Learning Sociology, Teacher Roles, Tolerance Attitudes.